2009
DOI: 10.1007/s10661-009-0917-6
|View full text |Cite
|
Sign up to set email alerts
|

Review of indicators and field methods for monitoring biodiversity within national forest inventories. Core variable: Deadwood

Abstract: Deadwood is one of the four elements taken into account in this review of indicators and field methods and is often considered as a key indicator of forest biodiversity. We have analysed the main types of surveys and have realised how greatly the needs and constraints used to monitor deadwood can vary among them. For instance, classical National Forest Inventories usually tend to avoid time-consuming collecting methods. In the wide variety of existing definitions of deadwood, such inventories require simple an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
18

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 32 publications
(32 reference statements)
0
66
0
18
Order By: Relevance
“…biomes, ecological regions, forests types, etc.) as well as the management policies in different Countries or areas (Hekkala et al, 2016;Korjus & Laarmann, 2015;Lassauce et al, 2011;Merganičová, Merganič, Svoboda, Bače, & Šebeň, 2012;Rondeux & Sanchez, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…biomes, ecological regions, forests types, etc.) as well as the management policies in different Countries or areas (Hekkala et al, 2016;Korjus & Laarmann, 2015;Lassauce et al, 2011;Merganičová, Merganič, Svoboda, Bače, & Šebeň, 2012;Rondeux & Sanchez, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of stumps, the basal diameter (D B ) and height (H) were measured. The length (L) and half-length diameter (D 1/2L ), as the main attributes (Rondeux and Sanchez 2009), were defined for lying dead trees. The diameter measurements were conducted using a circumeter, with an accuracy of 0.1 cm.…”
Section: Deadwood Measurementsmentioning
confidence: 99%
“…Due to the inability to determine the tree species to which decaying logs and stumps with very advanced decomposition belonged (decay classes 5 and 6 for stumps, decay class V for logs) and the failure to yield soil micronutrients by deadwood in the first two decay classes (Stokland et al 2004, Rondeux andSanchez 2009), only the third and fourth decay classes of dead trees were taken into account in the analysis. Moreover, the results were representative of each study site, as stumps in decay classes 3 and 4 and dead lying trees in decay classes III and IV were the most numerous ( Fig.…”
Section: Soil Investigationsmentioning
confidence: 99%
“…Surveys and monitoring of deadwood volume in forests provide useful indicators of habitat quality (Rondeux and Sanchez 2010). Previous research has shown that deadwood, whether standing or downed, constitutes an integral part of forest ecosystems, providing obligatory or facultative habitats for many organisms, such as bryophytes, lichens, fungi, and vascular plants (Dittrich et al 2014;Preikša et al 2015), as well as a variety of invertebrate and vertebrate animals (Bütler et al 2004;Stokland et al 2012).…”
Section: Introductionmentioning
confidence: 99%